Development of Acid-Base E-Modules Based on Guided Discovery Learning Using React Native to Improve Problem Solving Skills of Phase F High School Students - Rivo Juita Sudirman; Yerimadesi; Andromeda; Riga; Nofri Yuhelman (Jurnal Penelitian Pendidikan IPA, 2025)
The study aims to develop an acid-base e-module based on guided discovery learning using React Native to improve the problem-solving skills of senior high school students. The research method is Educational Design Research (EDR) using the Plomp model. The e-module using React Native is presented in the form of a mobile application that can be accessed on smartphones. The presentation of acid-base material in the e-module is adapted to the syntax of Guided Discovery Learning. The e-module was validated by 5 validators, including 3 subject matter experts and 2 media experts, using a questionnaire analysed with Aiken's V. Practicality was assessed by 9 students representing low, medium, and high ability categories using a questionnaire in the small group stage, analysed using achievement percentages. Effectiveness was determined by comparing pre-test and post-test scores of students using the N-gain formula. The validation results of the acid-base e-module using React Native were 0.90, categorized as valid, and the practicality of the e-module was 92%, categorized as highly practical. Effectiveness was obtained from N-gain data of 0.71, categorised as high (sufficiently effective). Hypothesis testing was conducted using the Wilcoxon test because the data was not normally distributed, with a sign of < 0.001, indicating that the acid-base e-module based on guided discovery learning using React Native can improve the problem-solving skills of senior high school students in phase F.